Effect of Saturation of Sandy Soil on the Displacement Amplitude of Soil Foundation System under Vibration (Journal of Engineering, 2015)
In this study, the response and behavior of machine foundations resting on dry and saturated sand was investigated experimentally. A physical model was manufactured to simulate steady state harmonic load at different operating frequencies. The effect of relative density, depth of embedment, foundation area as well as the imposed harmonic load was investigated. It was found that the amplitude of displacement of the foundation increases with increasing the amplitude of dynamic force and operating frequency meanwhile it decreases with increasing the relative density of sand, degree of saturation, depth of embedment and contact area of footing. The maximum displacement was noticed at 33.34 to 41.67 Hz. The maximum displacement amplitude response of the foundation resting on dry sand models is more than that on the saturated sand by about 5.0 to 10 %.